Henna@Printer / Nurul Atikah Badrol Hisham - Badrol Hisham, Nurul Atikah (2020)
GreeN@ company is a small running company which mainly focus producing a high quality of printer which base in organic henna as the ink which is HENN@PRINTER. By the name of the company, we want to show that, the company is producing a safe product which combine the natural organic product and electronic product at the same time. Our company is targeting to supply a unique organic henna printer as nowadays, people are love to have a unique and exclusive design of henna for any occasion such as wedding ceremony, engagement and even in Eid, Thaipusam and Deepavali celebration. Even though the process looks easy to make, but there must be some difficulty to produce a beautiful and perfect henna details. Therefore, only professional henna artist who has high experience in henna design could produce a well-designed henna and somehow to rent them require a lot of money and takes a lot of time to be done. Therefore, our company has produced a product which not just can help the henna artist but any people who wish to having an exclusive henna design for any occasion and at any time. Moreover, our marketing strategy would involve business strategy, marketing philosophy, the channel of distribution and the value chain of target market. The company main target market is on printer company at an urban area in Petaling Jaya Plus, we also target henna artist. Finally, the product that we produce can reduce time usage for producing a nice henna design. Furthermore, the price of the product is affordable. The price of our product is RM 471.48per/unit. Our company has targeting RM 1, 806, 239 of production by the second year of business.